DPPH free radical scavenging activity and phenotypic difference in hepatoprotective plant (Silybum marianum L.). (June 2013) - Ahmad, Nisar; Fazal, Hina; Abbasi, Bilal Haider; Anwar, Shazma; Basir, Abdul
Silybum marianum L. is medicinally important for its active principle component silymarin. Silymarin regenerates damaged hepatic tissues. On the basis of such regenerative properties, the radical scavenging activity (1, 1-diphenyl-2-picrylhydrazyl (DPPH)) of different tissues and the phenotypic difference of the hepatoprotective species, S. marianum L. were evaluated. There was less phenotypic difference in purple and white varieties of S. marianum. Assay of the antioxidant potential of different parts of the plant revealed that significantly higher activity (78.2%) was observed in seeds of the purple flowering plant than seeds of white flowering plant (49%) after different time intervals. Young leaves collected from white flowering plant exhibit 64.8% activity, which is higher than the purple flowering plant (55.1%). Significantly, same activity was observed in mature leaves of white (52%) and purple flowering plants (50%). The main stem collected from both the varieties exhibits similar activity from 50 to 52%. A 67.2% activity was recorded for mature roots of white flowering plant followed by roots of the purple variety (65%). The present study revealed that seeds and roots of both the varieties scavenge and detoxify more DPPH free radicals than other plant parts and can be used as a source of natural antioxidants and food additives.